Physical and Optical Behavior of Turmeric in Aqueous Media: A Literature Review - Said, Sukmawati (Pinisi: Physics Journal, 2025)
The phenomenon of mixing turmeric in water is widely used as a simple science experiment to introduce basic concepts of physics and chemistry. However, the physical behavior of curcumin—the primary pigment in turmeric—is complex and influenced by various physical principles, including diffusion, optics, thermodynamics, and molecular dynamics. This literature review aims to synthesize and analyze scientific findings related to turmeric–water interactions from the perspective of fundamental physics. By reviewing national and international research articles, this study identifies the diffusion mechanism of curcumin as described by Fick’s Law, its optical properties responsible for light absorption and color appearance, and the physical factors—such as temperature, pH, and light exposure—that affect curcumin stability in aqueous media. Additionally, the review highlights the roles of Brownian motion and solute–solvent molecular interactions in explaining the microscopic behavior of curcumin particles. The findings indicate that the “turmeric in water” phenomenon is not merely a simple mixing process but involves complex physical dynamics suitable for use as phenomenon-based learning material in science education. This study provides a strong theoretical foundation for the development of educational experiments and opens avenues for future research on the physical characteristics of natural pigments.